2020
DOI: 10.1177/1745506520949419
|View full text |Cite
|
Sign up to set email alerts
|

Health system experiences of breast cancer survivors in urban South Africa

Abstract: Background: Breast cancer is the most common cancer globally and among South African women. Women from socioeconomically disadvantaged South African communities more often present later and receive total mastectomy compared to those from more affluent communities who have more breast conserving surgery (which is less invasive but requires mandatory radiation treatment post-operatively). Standard chemotherapy and total mastectomy treatments are known to cause traumatizing side effects and emotional suffering am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…Another dimension for justifying the need for targeted education as core element in effective breast cancer control programmes, as supported by findings of this study, is that it would debunk ignorance and myths associated with breast cancer, since significant proportion of this study respondents identified psychosocial factors as barrier to mammography uptake. This notion corroborates the findings in other studies where low uptake of mammography was attributed to embarrassment from the procedure, fear from painful sensation, fear of cancer diagnosis, fear from exposure to radiation and spousal refusal [ 23 , 31 ]. Furthermore, the need for awareness creation in breast cancer control programmes is underscored by a significant proportion of respondents in this study who reported that they would uptake a mammography screening if encouraged by healthcare providers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Another dimension for justifying the need for targeted education as core element in effective breast cancer control programmes, as supported by findings of this study, is that it would debunk ignorance and myths associated with breast cancer, since significant proportion of this study respondents identified psychosocial factors as barrier to mammography uptake. This notion corroborates the findings in other studies where low uptake of mammography was attributed to embarrassment from the procedure, fear from painful sensation, fear of cancer diagnosis, fear from exposure to radiation and spousal refusal [ 23 , 31 ]. Furthermore, the need for awareness creation in breast cancer control programmes is underscored by a significant proportion of respondents in this study who reported that they would uptake a mammography screening if encouraged by healthcare providers.…”
Section: Discussionsupporting
confidence: 91%
“…[ 30 ] also observed that marital status was not independently associated with disease morbidity and mortality. It is generally believed that those who are married tend to utilize health services better than the singles, probably due to the support and reinforcement of addressing health needs by significant others [ 31 ]. This notion is supported by the findings in this study where significant proportion of respondents identified encouragement by family members as a potential facilitator of mammography uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this is also consistent with other African populations. Studies in Uganda, Nigeria, Eswatini and South Africa have all previously identified financial strain as major contributors to distress, non-adherence with cancer related care or both [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize surgical trauma and promote recovery, breast cancer surgery has evolved from radical surgery and extended radical surgery to modified radical surgery and breast-conserving surgery (1)(2)(3)(4). However, for patients with more diffuse lesions, breast-conserving surgery is less safe, but the loss of the breast can also be very psychologically taxing for the patient (5)(6)(7). Breast reconstruction surgery is becoming an increasingly popular alternative.…”
Section: Introductionmentioning
confidence: 99%